Features of connections between empathic abilities and conflict behavior - Xenia Gruzynova, (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
There is the research about finding connections and correlations between levels of display empathic abilities, dominant strategies of conflict behavior and level of intrapersonal conflict. In our research we used V. Boyko's diagnostic method of empathy abilities, K. Thomas' diagnostic method of individual predisposition to conflict behavior and Е. Fantalova's diagnostic method "Level ratio "values" and "accessibility" in various spheres of life". The respondents of this research were42 students and data processing was made by help of statistic computer program SPSS.
Keywords: conflict behavior, strategy, intrapersonal conflict, empathy, empathy channels, correlation.